Totally laparoscopic esophago-gastrectomy - Costi, R.; Himpens, J.; Essola, et al., B. (Acta Biomedica Atenei Parmensis, 2004)
The recent progress of surgical endoscopy has allowed to perform minimally invasive esophagectomy both by a combined laparoscopic/thoracoscopic and a totally laparoscopic transhiatal approach. Up to now, all these techniques imply a thoracic (or thoracoscopic) and/or cervical access to perform the esophagogastric anastomosis. In the presented case, a 44-year-old white male patient affected by adenocarcinoma of the cardia (Siewert type 2) underwent a distal esophagectomy entirely accomplished by laparoscopy (including the realization of a mechanical intrathoracic esophagogastrostomy), without the need of any thoracic (nor thoracoscopic) nor cervical access. Duration of surgery was 407 minutes. Postoperative course was uneventful and the patient was discharged on day 7. In selected cases, a totally laparoscopic esophago-gastrectomy without thoracic nor cervical access, may improve the patient’s outcome